Stretchable E‐Skin Apexcardiogram Sensor. Issue 30 (11th May 2016) - You, Insang; Kim, Bongsoo; Park, Jaeyoon; Koh, Kunsuk; Shin, Sangbaie; Jung, Sungjune; Jeong, Unyong
Abstract : A new strategy to measure the apex cardiogram with electronic skin technology is presented. An electronic skin apexcardiogram sensor, which can compensate the conventional electrocardiogram for cardiac diagnosis, is demonstrated through a highly sensitive and stretchable strain sensor with gold‐nanoparticle composites.